THE BANKING SYSTEM IN THE WORLD - Gulshan Sattarova (Scholars Digest Publishing, 2023)
The article discusses about the banking systems in the world and the main functions of financial institutions.
Keywords: banking system, loans, financial institutions, interest rates, residents, financial transactions, banknotes.